EFEKTIFITAS KUNJUNGAN NIFAS TERHADAP KETIDAKNYAMANAN FISIK YANG TERJADI PADA IBU MASA NIFAS - Wardini Puji Lestari, Sri (JURNAL KEPERAWATAN BINA SEHAT, 2016)
During recovery, mother will many experience, both physically and psychologically is largely physiological fact, but if it isn’t through the facilitation of midwifery care then it is possible there will be a pathological condition. The purpose of this study to determine the effectiveness of postpartum visits to the physical discomfort that occurs in the mother during childbirth.This research Design is analytic correlational with cross sectional approach. The research variables are postpartum visit was independent variables and physical discomfort as dependent variable. The population is all postpartum women who visit at BPS Mrs. Hj. Nikmah, M Jombang. were 37 postpartum mothers. Samples collected by saturated sampling as much as 37 respondents. Data were collected with a checklist and chi square test.The results showed that effectiveness of postpartum visits to the physical discomfort that occurs in women during childbirth that show of the chi-square test statistic indicates ρ = 0.04 and α = 0.05, it can be stated ρ <α, so that H1 is accepted meaning There is effectiveness of postpartum visits to the physical discomfort that occurs in the mother during childbirth.If mothers do more postpartum visits will be more discomfort and if the reduce postnatal visits will discomfort is abnormallity. The conclusion are the better postpartum visits diminishing the discomfort felt. Hopefully health workers are to improve their motivation and health education about postnatal discomfort that should be seen in the importance of postnatal visits is expected to motivate postpartum women to be more active in postnatal visits.Key Words : Physical Discomfort, Post Partum